2018 FHTM publication statistic / Irina Mohd Akhir - Mohd Akhir, Irina (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
I am pleased to inform that according to publication PRISMA report for 2018 (Fig.l), journal publications are at 73% (indicating the publication priority), while proceedings are at 21%. Subsequently, there is an improvement in SCOPUS indexed journals entries and hopefully this will continue to improve in 2019. Furthermore, a book was published in 2018 and this contributed to 3% of the total percentages of all types of publications. However, there was no contributions for general publications. The editorial board is optimistic that there will be more publications happening in 2019 and in the years to come.